Effect of fermented food consumption on biochemical parameters and adipokines levels - Gezginç, Yekta; Marancı, Canan (Progress in Nutrition, 2018)
Background/aims: The aim of this study was to determine how fermented food consumption affected the presence of changes in Adipokines levels such as apelin-13, leptin and adiponectin, besides some biochemical parameters. Methods: For this purpose, 23 healthy women and men were selected. Blood samples taken from 12 female and 11 male whose ages ranged between 19 and 25 years before and after kefir consumption, and apelin-13, leptin and adiponectin were analyzed from adipokines besides routine biochemical parameters. Results: The decrease in LDL cholesterol levels which are an indicator of endogenous cholesterol production was found significant (p